أضرار المخدرات على العقل في ضوء المقاصد القرآنية - Abdo Khaled, Nashwan (2014)
ABSTRACT This research aims at exposing the side effects and harm of drugs on human health in general and human mind in particular. The research is based on the objectives of the Quran forbidding this issue in order to reveal its clandestine and objectives which has emerged as an Islamic approach with a vast experience and as role model in changing human being.